Asymmetric Synthesis of α-Alkylated γ-Lactam via Nickel/8-Quinim-Catalyzed Reductive Alkyl-Carbamoylation of Unactivated Alkene - Wu, Xianqing; Shrestha, Mohini; Chen, Yifeng (Synlett, 2021)
Chiral-auxiliary-mediated synthesis represents the most frequently used synthetic tool for the induction of chirality on α-position of γ-lactams in organic synthesis. However, the general strategy requires the stoichiometric use of chiral reagents with multiple manipulation steps. Transition-metal-catalyzed asymmetric alkene dicarbofunctionalization using readily available substrates under mild conditions allows the simultaneous construction of two vicinal chemical bonds and a chiral carbon center, hence, gain expedient access to chiral heterocycles. Herein, we disclose a Ni-catalyzed enantioselective reaction of 3-butenyl carbamoyl chloride and primary alkyl iodide enabled by a newly designed chiral 8-quinoline imidazoline ligand (8-Quinim). This protocol features broad functional group tolerance and high enantioselectivities, achieving unprecedented synthesis of chiral nonaromatic heterocycles via catalytic reductive protocol.1 Introduction2 Development of 8-Quinim Ligand3 Nickel/8-Quinim-Catalyzed Enantioselective Synthesis of Chiral α-Alkylated γ-Lactam4 Conclusion and Outlook
Keywords: 8-Quinim; nickel catalysis; reductive coupling; unactivated alkene; dicarbofunctionalization; chiral α-alkylated γ-lactam synthesis